2022
DOI: 10.1155/2022/9295326
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Ablative Strategy for Atrial Fibrillation: A State-of-the-Art Review

Abstract: In spite of technological progress and the improving skills of operators, atrial fibrillation (AF) ablation results appear to date to be at a plateau. In any case, the superiority of ablation over pharmacological therapy in terms of effectiveness, reduction of hospitalizations, and improvement has been well demonstrated in recent randomized trials. Triggers, substrate, and modulating factors (elements of Coumel’s triangle) play different roles in paroxysmal and persistent AF, so induction and perpetuation mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…It is well known that arrhythmogenic mechanisms beyond the pulmonary veins are often involved in patients with PeAF. The prevailing CA strategies beyond PVI for PeAF include targeting mechanisms and anatomical ablation, and recently, Zefferino Palam et al have well summarized the current CA strategies in this article [ 21 ]. CFAEs and rotor ablation have been developed in the past ten years to eliminate PeAF, but did not demonstrate more benefits than PVI alone.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that arrhythmogenic mechanisms beyond the pulmonary veins are often involved in patients with PeAF. The prevailing CA strategies beyond PVI for PeAF include targeting mechanisms and anatomical ablation, and recently, Zefferino Palam et al have well summarized the current CA strategies in this article [ 21 ]. CFAEs and rotor ablation have been developed in the past ten years to eliminate PeAF, but did not demonstrate more benefits than PVI alone.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the evolution of the APs properties over time is not absolutely predictable and, moreover, we must not forget that the presence of an AP in itself can increase the risk of AF since it increases the intra-atrial refractoriness dispersion 25 ; thus, APs represent an excellent ablative target in the context of tailored AF treatment. 26 So far we have made some speculations on the pediatric population on which we have considerable studies, which however are lacking on the adult population. For the latter, we have only reports showing cases of patients with intermittent ventricular pre-excitation and APs with high-risk characteristics or even cardiac arrest from VF.…”
Section: Current Intermittent Ventricular Pre-excitation Panoramamentioning
confidence: 99%
“…To this goal, we tried to evaluate whether an ablative approach, tailored on the patho-physiological mechanisms of the arrhythmia could provide optimal results, minimizing the procedural risks for patients. We demonstrated that some forms of paroxysmal atrial fibrillation can be triggered by other kind of arrhythmias with focal (atrial tachycardia) or reentrant mechanism (WPW syndrome or nodal reentrant tachycardia) (7)(8) . On the other hand, in patients with vagally-mediated AF we also investigated the possibility of using right atrial ganglion ablation to modify the influence of the autonomic nervous system on the heart, in order to prevent atrial fibrillation episodes (9) .…”
mentioning
confidence: 93%